Graduate Writing Assignments Across Faculties in a Canadian University - Shi, Ling; Dong, Yanning (Canadian Journal of Higher Education, 2015)
This study examines 143 graduate assignments across 12 faculties or schools in a Canadian university in order to identify types of writing tasks. Based on the descriptions provided by the instructors, we identified nine types of assignments, with scholarly essay being the most common, followed by summary and response, literature review, project, review, case analysis, proposal, exam, and creative writing. Many assignments are instructor-controlled and have specific content requirements. Some are also process-oriented, providing students with teacher or peer feedback on outlines or initial drafts, suggestions for topic choices, and examples of good writing. With an overview of the types of writing tasks across campus, the study has implications for English for Academic Purposes (EAP) or graduate writing program designers, material developers, educators working within and across disciplines, and researchers interested in the types of university writing assignments in Canada.